Post Stabilization Inflation Dynamics in Slovenia - Ross, Kevin (IMF Working Papers; Working Paper, 1998)
This paper investigates the inflation process in Slovenia through an examination of some commonly used determinants of inflation in transition economies. Granger causality tests and an analysis of unrestricted VAR models suggest a strong linkage between both growth in broader monetary aggregates and changes in the tolar-deutsche mark exchange rate on retail price inflation. While the growth in wages affects inflation, it appears that both changes in the exchange rate and growth in monetary aggregates provide the initial impulse. A discussion of the present money-exchange rate policy framework and its influence on inflation is also provided.